Bioanalytical Method Development and Validation of an LC-MS/MS Method for the Quantitation of Fruquintinib in Rabbit Plasma - Manasa, Thota; Gandla, Kumaraswamy (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim: An LC-MS/MS method is needed to accurately measure the concentration of Fruquintinib in a biological sample. This method should be both specific and sensitive. Materials and Methods: The processed materials were separated using a Hypersil ODS C18 column (50 mm × 4.6 mm) 3.5 µm with a mobile phase of acetonitrile, methyl alcohol, and 0.1% HCOOH in the proportion of 20:70:10. The moveable solvent system was measured using a column with 0.7 mL/ min rate of flow. The drug and Internal Standard (IS), Dapagliflozin were assessed by monitoring the transitions of m/z -394.12/363.1 and 409.1/289.1 for Fruquintinib and IS, correspondingly, in multiple reaction monitoring mode. Results: The results of the linearity equation and the Correlation Coefficient (r 2 ) were as follows: y=0.0011x - 0.0022 and >0.99 correspondingly after the analysis. When compared to the reported methods in the rat plasma, those methods were in the linearity range of 93 (LLOQ) to 2710 (ULOQ) ng/mL in plasma with the %RSD values in between 2.4 to 4.51 which were poor as compared to the current method. It was discovered that the QC-samples (254, 1805 and 2160 ng/mL) had a relative standard deviation of between 2.49 and 4.24% for the intra and interday accuracy of the approach that was developed. The precision deviation values for intra and inter-batches were varied between 2.83 and 4.24 of relative standard deviations. At MQC, LQC, and HQC levels, an average Fruquintinib extraction recovery was 94.8%, 95.4%, and 94.7%, respectively. Average IS adjusted matrix factor for all the analytes was between 0.941 and 1.105, with a standard deviation of 4.99%. Conclusion: The new method was effectively used to the regular evaluation of Fruquintinib in biological materials, and it has been shown that Fruquintinib is more stable over a longer length of time
Keywords: Bio-Analytical Method; Fruquintinib; ICH Validation; LC-MS/MS Method; Quantitative; Determination; Rabbit Plasma; VEGFR